A manual for writers of term papers, theses, and dissertations - Turabian, Kate L. (University of Chicago Press, 1973)
Newly revised to conform with the Chicago Manual of Style, Turabian's Manual for Writers provides comprehensive, detailed, superior guidance to writers of research papers. From "Parts of the Paper" (including the niceties of copyrights and dedications) to "Sample Layouts," everything to do with format is covered. Mechanics of style (abbreviations to quotations) are reviewed, there's help on tables and illustrations, and chapters on bibliographies, parenthetical references, note taking, and citations. There are suggestions for manuscript preparation, hints on word-processing software, and formatting for research papers' more complex features. When you're up to your eyebrows in research data, it's a vast relief to have quick, accessible, reliable answers to your questions of structure, scholarly propriety, and academic style.